Common determinants of antimicrobial resistance in sequential episodes of sexually transmitted shigellosis in men who have sex with men: a cross-sectional study. (23rd February 2017) - Baker, Kate S; Dallman, Timothy J; Field, Nigel; Childs, Tristan; Were, John; Hughes, Gwenda; Jenkins, Claire; Thomson, Nicholas R
Abstract: Background: In high-income nations, men who have sex with men (MSM) are at increased risk of shigellosis. A sublineage of Shigella flexneri serotype 3a was recently shown to have spread worldwide in MSM, driven by mobilisable azithromycin resistance. Since then, the serotype 2a and the species S sonnei have become epidemic in the UK. We aimed to determine whether these subsequent outbreaks were also attributable to epidemic sublineages in MSM and mobilisable antimicrobial resistance. Methods: We applied whole-genome sequencing to a random cross-section of S flexneri 2a (n=176) and S sonnei (n=188) isolates submitted to the UK national reference laboratory between 2004 and 2014 (10% and 2% of travel-associated and 20% and 10% of domestically acquired cases, respectively). Phylogenetic analysis and patient data (date of illness, age, sex, travel history) were combined to identify potential MSM-associated sublineages, and antimicrobial resistance determinants were compared among S sonnei, S flexneri 2a, and pandemic S flexneri 3a. Findings: Shorter phylogenetic distances (more closely related isolates) were statistically associated with male–male patient pairs for both S sonnei and S flexneri 2a. For S flexneri 2a, this association manifested as a single low-diversity sublineage containing 47 of 176 isolates collected over the epidemic window (2012–2014) mainly (43 of the 47 isolates) from 16–60-year-old male patients without recent travel. This lineage was associated with azithromycin resistance (odds ratio 25·8, p<0·0001) carried by an antimicrobial resistance determinant identical to that found in the pandemic S flexneri 3a sublineage. For S sonnei there were multiple low-diversity sublineages with similar patient profiles, some of which were associated with this azithromycin resistance determinant. Interpretation: These results suggest that outbreaks of S flexneri 2a and S sonnei were associated with MSM. The mobilisation of azithromycin resistance between S flexneri 3a, S flexneri 2a, and S sonnei indicates that antimicrobial resistance has a role in driving these epidemic waves. The presence of a single resistance determinant associated with all three epidemics suggests that future antimicrobial resistance surveillance might be enhanced by focusing at the level of genetic determinants rather than pathogens. Funding: Wellcome Trust, Public Health England.